Spatial Mapping of Historical Flood Intensity Impacting Automotive Facilities in Jabodetabek - David Hasudungan Simangunsong; Anton Mulyono Azis (Eastasouth Institute, 2026)
Flooding is a recurring hydrometeorological disaster that has a significant impact on Jabodetabek, including the sustainability of the automotive industry as one of the country’s strategic sectors. This study aims to map the historical flood intensity and analyze its implications for automotive supply chain facilities. Sentinel-1 imagery was applied to detect inundation, complemented by permanent water body and built-up area masking from Sentinel-2, as well as the integration of spatial data on road networks and automotive facilities. The results indicate that more than 53% of the affected area experienced recurrent flooding (>25 times), with Bogor City, Bekasi Regency, and Tangerang Regency being the most extensively inundated regions. A total of 61% of automotive facilities were exposed to flooding, and 47% of the road network in Jabodetabek was inundated at least once over the past five years. These findings highlight systemic vulnerabilities that threaten the continuity of the Just-in-Time supply chain, marked by potential production delays, increased logistics costs, and reduced efficiency. This study recommends integrating spatial risk analysis into facility planning, strengthening infrastructure, providing alternative distribution routes, and leveraging GIS-based digital technologies to enhance visibility and resilience of the automotive supply chain in Jabodetabek.